Nanotechnology and nanosensors in personalized healthcare: A comprehensive review - Ghorbian, Mohsen; Ghobaei-Arani, Mostafa; Babaei, Mohamad Reza; Ghorbian, Saeid (Sensing and Bio-Sensing Research, 2025)
Healthcare is one of the most essential fields in providing accurate and fast medical care. With the advancement of technology, nanosensors have become a new tool that has enabled early diagnosis and continuous monitoring of diseases with high accuracy. With the ability to identify molecular and cellular changes, nanosensors can accurately detect biomarkers of diseases even in the initial stages and provide detailed information about the state of the body, especially in complex and costly diseases such as cancer. However, in this process, there are challenges such as biocompatibility and long-term stability of nanosensors in biological environments, immune reactions, and the possibility of their destruction. The present article has identified the challenges and evaluated the new methods of this technology by systematically reviewing the application of nanosensors in healthcare. This article aims to provide a comprehensive view of how to use nanotechnology as nanosensors in healthcare. The findings show that using nanosensors in the healthcare field can increase the accuracy of disease diagnosis (ADD) by 35 % and improve the quality of personal health monitoring (PHM) by 23 %. Also, this technology has reduced diagnostic response time (DRT) by 21 %. Finally, this research has taken a practical step towards further developing the application of nanosensors in the healthcare field by providing valuable recommendations and examining open issues.